A Simple Approach for Evaluating Slope Movements Induced by Groundwater Variations. (2016) - Conte, Enrico; Troncone, Antonello; Donato, Antonio
Abstract: Landslides reactivated by groundwater variations are usually characterized by low displacement rate with deformations essentially concentrated within a narrow shear zone above which the unstable soil mass moves like a rigid body. A simplified method was recently proposed by Conte and Troncone[1] for a preliminary evaluation of the mobility of these landslides. In the present study, this method is extended by incorporating a calibration procedure for a direct evaluation of some parameters which are difficult to obtain experimentally. Some case studies are analysed to validate the present approach.